Colorectal cancer : evidence-based chemotherapy strategies - Saltz, Leonard B (Humana Press, 2007)
Recent advances in the understanding of the biology of colorectal cancer have radically transformed the treatment options available to clinicians, leaving textbooks written only two years ago completely out of date. This evidence-based and data-driven guide presents reviews of cutting-edge therapies for colorectal cancer, all articulated by leading experts in the field. This integrated and focused consideration of colorectal management includes reviews of cytotoxic chemotherapy, targeted biologic therapies, as well as updates on adjuvant chemotherapy for colon cancer and combined modality management of rectal cancers. Attention is also focussed on the role of potentially curative multi-modality management of liver metastases, with considerations of the role of liver resection and discussions of non-surgical ablative therapies. Supportive issues are also considered, including contributions from experts in pain management and oncology nursing. The reviews presented here are concise, up-to-date, and are organized with the treating practitioner in mind. Opening chapters outline contemporary thinking on the biology of colorectal cancer, and methods of possible prevention utilizing chemoprevention and screening. Subsequent chapters present cutting-edge uses of cytotoxic chemotherapy and review the potential for incorporating innovative biological therapy. Ample consideration is given to practical issues related to colorectal chemotherapy, specifically radiological evaluation of colorectal cancer treatment and supporting patients through chemotherapy, including pain management. The concluding chapter is devoted to the exploration of and implications of emerging new drug paradigms and their potential impact on colorectal cancer treatment. This unique text offers the practitioner a concise, authoritative reference, so that recent advancements and understanding may be digested, disseminated, and rapidly applied to the treatment of the colorectal cancer patient.
Current clinical oncology
Keywords: Colorectal Neoplasms; protokoly protinádorové kombinované chemoterapie; kolorektální nádory; gastroenterologie; Evidence-Based Medicine; medicína založená na důkazech; farmakoterapie; Drug Therapy; Antineoplastic Combined Chemotherapy Protocols; onkologie